THE ORIGIN OF THE ETHNONYMS BURTI AND SULI - Amirhanov, Hizri Amirhanovic (History, Archeology and Ethnography of the Caucasus, 2024)
The ethnogenesis and ethnic history of the peoples of the North-Eastern Caucasus remain a fascinating yet underexplored area of historical Caucasian studies. This article proposes a hypothesis regarding the origin of two ethnonyms: suli, used by the Chechens to designate Dagestanis (particularly Avars), and burti, employed by the Avars to refer to the Chechens. The author posits that the ethnonym suli derives from the Sal (Salar) people, who resided in the foothills of Northern Dagestan until approximately the late 15th century, during the decline of the Golden Horde. This group maintained direct contact with the Avar ethnic community before being assimilated into the latter’s traditional habitat. Fragments of the Sal people, who had settled in the northern Dagestani foothills, gradually integrated into the Avar and Andi (an Avar subethnic group) territories. While the Sal were eventually absorbed, their name persisted in the form suli, used by the Chechens to denote Dagestanis. Ethnic identification in the North-Eastern Caucasus during this period typically involved extending the names of specific adjacent segments of an ethnic community (tribes, clans) to the entire people. In this case, the Avars were the southern and eastern neighbors of the Chechens (in the indicated period, though, this ethnonym did not yet exist). The specific community with which the latter interacted with the Chechens should have been an ethnic group (teip?, tukhkum?) with the root but in its name (possibly pronounced as butoi). This interaction gave rise to the Avar-Andi designation for the Chechens: burtiyal (or buturul). From the second half of the 17th century, the Avars began using the ethnonym chachanal (Chechens) alongside burtiyal, though the latter has not been entirely forgotten. Similarly, the Chechens retained the ethnonym suli for the Avars, which, despite its seemingly obscure history, appears to be explicable through this analysis.